The Role of the PKPR Program (Youth Care Health Services) on Reproductive Health Youth in Bengkong District - Nuari Andolina; Fitriani Fitriani; Helly Devie Yanita (UIMA Press, 2021)
Background: The implementation of the PKPR program in Indonesia is still not running as expected, the Youth Care Health Program is a health program aimed at teenagers and becomes one of the forums to solve the problems they face. Objectives: The purpose of this study was to determine the role of the PKPR program in Bengkong District Methods: The design of this research is a descriptive qualitative study with a phenomenological approach, conducted in Bengkong District in 2022, collecting data by Focus Group Discussion (FGD) and in-depth interviews with 5 informants and focus group discussions with 10 informants in order to obtain information regarding the implementation of the health care program. adolescents while data validation was done by triangulation of sources and triangulation of methods. Results: The results showed that the implementation of PKPR in Bengkong District was guided by the guidebook issued by the Indonesian Ministry of Health, funds for the implementation of PKPR were sourced from DAK, BOK, and funding from UKS. Conclusion: Conclusion Research on the existence of policies from the Bengkong District government and cooperation with all cross-sectors in providing health education so that the implementation of this program runs optimally.